EXTRAPERITONEAL LAPAROSCOPIC RADICAL PROSTATECTOMY: INITIAL EXPERIENCE AND LEARNING CURVE OF A VERY LOW VOLUME CENTER - Yunir, Peri Eriad; Hamid, Agus Rizal AH; Umbas, Rainy; Mochtar, Chaidir Arif (Indonesian Journal of Urology, 2017)
Objective: This study is aimed to report and evaluate the experience and learning curve of extraperitoneal Laparoscopic Radical Prostatectomy (LRP) performed in Cipto Mangunkusumo General Hospital Jakarta. Material & method: We collected all data of patients that had been performed extraperitoneal LRP from June 2013 until February 2016, retrospectively. We divided those data into 3 groups with equal number in each group. We compared the preoperative (age, prostate volume, PSA level and prostate cancer staging), intraoperative (surgery time, total blood loss, conversion to open surgery and other organ injury), and postoperative (postoperative length of stay) variables between those 3 groups using ANOVA and Kruskal-Wallis test. Results: We performed 15 extraperitoneal LRP from June 2013 until February 2016 with patient’s mean age was 64.40 (SD ± 5.30) years old and mean prostate volume was 42.39 (SD ± 29.21). In this study, we found significant differences in surgery time, total blood loss, and postoperative length of stay (LOS) in all group with decrease on each intraoperative and postoperative variables. We also found no conversion to open surgery or other organ injury in all patients. Conclusion: The increase of surgeon’s experience and the number of surgery, and the consistency undergo the procedure of LRP demonstrate a decrease in surgery time, intraoperative blood loss and LOS in LRP patients.